The development of Slovenian music in european discourse - KRIŽNAR, FRANC (Pomurska obzorja, 2026)
The following places Slovenian music in time and space, from antiquity to the present. In the context of European comparisons of this kind, Slovenian music has fluctuated continually in terms of performance and creativity; lagging behind, then equaling or even surpassing European music. From its very beginnings to the present day, Slovenian music has been interesting: On the one hand, it attracted the rest of Europe; on the other hand, the rest of European music was so interesting for Slovenian music that it faced it at home, on Slovenian soil. All this is shown chronologically and stylistically from its alleged and proven beginnings through the Middle Ages, the Renaissance, the Baroque, the Rococo – from the Wild Hags with a bone flute to the Baroque, classical, romanticism, modernism, modernisms of the 20th and 21st centuries, and their reflections in Slovenia – to the conclusion. The emergence of Slovenian music over two millennia is shown in the religious and secular spheres, through vocal, instrumental and vocal-instrumental music. All these musically relevant areas are shown with specific and selected creators/authors and performers of their music. Characteristic and different stylistic orientations, along with the nations of their European representatives, are highlighted.
Keywords: Slovenian music history; European influences; Stylistic development; Religious and secular music; Vocal and instrumental traditionnturies